SISTEM INFORMASI AKUNTANSI DALAM PENYAJIAN AUDIT FINANCIAL REPORT DENGAN MENGGUNAKAN COMPUTER ASSISTED AUDIT TECHNIQUES (CAATs) - Nur Azizah; Ferry Sudarto (CommIT (Communication and Information Technology) Journal, 2010)
The use of computerized technology in the current globalization era has become more rapid therefore assisting all activities in all fields, especially in the financial audit report in an accounting information system. Many problems were encountered with the auditors in conducting audits using conventional methods in an electronic data processing environment. However, these constraints are often ignored and do not get serious attention even by the auditors themselves. Inefficiencies resulted is often not oblivious. Therefore, constraints that occurred can be solved with a variety of ways, including the usage of Computer Assisted Audit Technique (CAATs) through a test data approach and Parallel Test Facility (PTF).Keywords: audit financial report, CATTs, accounting information system